Analyzing Visual Metaphor and Metonymy to Understand Creativity in Fashion - Uno, Ryoko; Matsuda, Eiko; Indurkhya, Bipin (Frontiers in Psychology, 2019)
The role of figurative languages such as metaphor and metonymy in creativity has been studied in cognitive linguistics. These methods can also be applied to analyze non-linguistic data such as pictures and gestures. In this paper we analyze fashion design by focusing on visual metaphor and metonymy. The nature of creativity in fashion design is not fully studied from a cognitive perspective compared to other related fields such as art. We especially focus on the aspect of fashion design as a communication tool between the designer and the audience to convey designer’s image of human. Photos from two fashion shows are analyzed. We carried out an experiment to compare how human images in two shows are interpreted by those who are familiar with fashion and those who are not. We got three results: (1) As far as figurative (metaphorical and metonymic) interpretations of human image are concerned, two groups with different familiarity to fashion have significantly different patterns of responses to two shows. (2) For non-figurative interpretations (such as physical or personal attributes), no significant difference in the pattern of response to the show was observed between two groups. The participants as a whole, however, responded to the two shows differently. (3) In addition for non-figurative interpretation, fashion experts found significantly more attributes in human images than the others. The results show that the analysis of figurative interpreations is effective in seeing how the familiarity to fashion affects the mode of seeing fashion shows.